Multiple‐dose, safety, pharmacokinetic, and pharmacodynamic study of sotatercept (ActRIIA‐IgG1), a novel erythropoietic agent, in healthy postmenopausal women. (9th September 2013) - Sherman, Matthew L.; Borgstein, Niels G.; Mook, Louisa; Wilson, Dawn; Yang, Yijun; Chen, Nianhang; Kumar, Ravindra; Kim, Kenneth; Laadem, Abderrahmane
Abstract Ligands of the transforming growth factor‐beta superfamily and activin‐receptor signaling play an important role in erythropoiesis. Sotatercept, an activin receptor type IIA (ActRIIA) ligand trap, is a novel, recombinant, fusion protein comprising the extracellular domain of human ActRIIA linked to the Fc portion of human immunoglobulin G1. Sotatercept, originally developed to increase bone mineral density, was noted to have robust effects on erythropoiesis. Here, we evaluated the safety, pharmacokinetic properties, and pharmacodynamic effects of sotatercept in 31 healthy postmenopausal women. Sotatercept was administered at dose level 0.1, 0.3, or 1 mg/kg every 28 days subcutaneously for up to four doses. Sotatercept was generally safe and well tolerated, and elicited clinically significant, dose‐dependent increases in hemoglobin, hematocrit, and red blood cell counts that persisted for up to 4 months. The effect of sotatercept on hemoglobin was dose‐limiting. Sotatercept also increased bone mineral density and biomarkers of bone formation. The sotatercept serum exposure–dose relationship was linear, with a mean terminal half‐life of approximately 23 days. ActRIIA ligands are important regulators of erythrocyte production in healthy individuals. Clinical studies are ongoing to explore the potential of sotatercept to treat anemia and diseases of ineffective erythropoiesis as well as an agent to increase bone mineral density.